Structural dynamics and susceptibility of anti-HIV drugs against HBV reverse transcriptase. Issue 7 (9th April 2021) - Kammarabutr, Jirayu; Mahalapbutr, Panupong; Okumura, Hisashi; Wolschann, Peter; Rungrotmongkol, Thanyada
Abstract: Hepatitis B virus (HBV), a small enveloped DNA virus, attacks the human liver causing both acute and chronic diseases. Current therapeutic drugs use the nucleos(t)ide analogues (NAs) as a competitive inhibitor against HBV reverse transcriptase (HBV-RT), an essential enzyme pivotally involved in viral replication. Unfortunately, this treatment still causes the development of resistant variants of HBV against NAs. As HBV-RT is homologous to the human immunodeficiency virus reverse transcriptase (HIV-RT), it is reasonable to treat HBV-RT with anti-HIV drugs. In the present study, we aimed to investigate the structural dynamics and susceptibility of the known anti-HIV drugs (stavudine [d4T], didanosine [DDI], and zidovudine [ZDV]) against HBV-RT enzyme in comparison to the anti-HBV drug lamivudine (3TC) and deoxythymidine triphosphate (dTTP) substrate using several computational approaches. The Δ G bind residue calculations revealed that seven polar residues (K32, R41, D83, S85, D205, N236, and K239) and three hydrophobic residues (A86, A87, and F88) of HBV-RT as well as the adjacent DNA strands play an important role in the ligand binding. In addition, the H-bond pattern of d4T is similar to that of 3TC, especially at the residues A86 and A87. Such interactions promote the favorable conformation of ligand in the HBV-RT binding pocket, while the several different conformations of ligand are found in the unbound state. The predicted binding free energy results based on QM/MM-GBSA and MM/GB(PB)SA methods suggested that the susceptibility towards HBV-RT of d4T and ZDV is higher than that of 3TC and dTTP. Altogether, this work sheds light on the potentiality of d4T and ZDV as a promising drug for HBV-infected patients harboring 3TC resistance. Communicated by Ramaswamy H. Sarma